Optimisation of enzymatic protein hydrolysis of mud crab (Scylla sp.) to obtain maximum angiotensin-converting enzyme inhibitory (ACEI) activity using response surface methodology - Zaliha Harun,; Amiza Mat Amin,; Norizah Mhd Sarbon,; Mohamad Khairi Mohd Zainol, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Optimisation is commonly employed to find the conditions that produce the best possible response, thus minimizing the cost and time of a particular process. Response Surface Methodology (RSM) is a widely used tool in optimisation. This study reported the optimisation of enzymatic hydrolysis of mud crab meat using RSM by employing a face-centered Central Composite Design (CCD) to obtain maximum angiotensin-converting enzyme inhibitory (ACEI) activity. Screening of commercial food grade proteinases was carried out using Alcalase®, Protamex®, Neutrase® and papain shows that Protamex® gave the highest ACEI activity. The enzymatic hydrolysis conditions used in the optimisation were temperature (45-65ºC), pH (pH 5.5-7.5), hydrolysis time (1-4 hours) and Protamex® enzyme to substrate (E/S) ratio (1-3%). It was found that quadratic model was able to explain the relationship between the hydrolysis conditions and ACEI activity. The optimum conditions were obtained at 65ºC, pH 5.6, 1% E/S ratio and 4 hours of hydrolysis time. The experimental ACEI activity (88.93±1.02%) was not significantly difference (p>0.05) with the predicted ACEI activity (91.10%). It was found that the IC50 of the mud crab hydrolysate prepared at optimum condition was 1.96±0.13 mg/mL. This study shows that RSM can be used to explain the relationship between enzymatic hydrolysis conditions of mud crab meat and its ACEI activity.